Analysis of the functional muscle–bone unit of the forearm in patients with phenylketonuria by peripheral quantitative computed tomography. Issue 2 (22nd November 2016) - Choukair, Daniela; Kneppo, Carolin; Feneberg, Reinhard; Schönau, Eckhard; Lindner, Martin; Kölker, Stefan; Hoffmann, Georg F.; Tönshoff, Burkhard
Abstract: Bone disease in patients with phenylketonuria (PKU) is incompletely characterized. We therefore analyzed, in a cross‐sectional study radius macroscopic bone architecture and forearm muscle size by peripheral quantitative computed tomography (pQCT) and muscle strength by hand dynamometry in a large cohort ( n = 56) of adolescent and adult patients with PKU aged 26.0 ± 8.9 (range, 11.8–41.5) years. Data were compared with a reference population ( n = 700) from the DONALD study using identical methodology. We observed a significant reduction of cortical thickness (z‐score −1.01 ± 0.79), Strength–Strain Index (SSI) (z‐score −0.81 ± 1.03), and total bone mineral density (BMD) of the distal radius (z‐score −1.05 ± 1.00). Mean muscle cross‐sectional area (z‐score −0.98 ± 1.19) and muscle grip force (z‐score −0.64 ± 1.26) were also significantly reduced, indicating an impaired muscular system as part of the clinical phenotype of PKU. SSI positively correlated ( r = 0.53, P < 0.001) with the corresponding muscle cross‐sectional area in the reference population; however, the regression line slope in PKU patients was less steep ( P < 0.001), indicating that bone strength is not adequately adapted to muscle force. In conclusion, the radial bone in PKU patients is characterized by reduced bone strength in relation to muscular force, decreased cortical thickness, and impaired total BMD at the metaphyseal site. These alterations indicate a mixed bone defect in PKU, both of which are due to primary alterations of bone metabolism and to secondary alterations in response to neuromuscular abnormalities.